Digital Forensic Legal Study in Proving Criminal Defamation Cases (Decision Study Number 8/PID.SUS/2021/PN MSH) - Maulana Putra; Risdalina Risdalina; Indra Kumalasari M (CV. AFDIFAL MAJU BERKAH, 2025)
The method used in this study is normative legal research, which focuses on analyzing legal issues by referring to applicable regulations related to the study of digital forensic law in proving defamation cases. This research is based on Decision Number 8/Pid.Sus/2021/PN Msh, which highlights the crucial role of digital forensics in revealing evidence and determining the defendant's accountability. In this case, the defendant, ALI TUAHAN, was accused of defamation through a Facebook post using the account